Persepsi Dosen Pendidikan Agama Islam Terhadap Rendahnya Sikap Toleransi di Kota Banda Aceh - Heru Syahputra; Anton Widyanto; Sri Suyanta (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
Tolerance is the key to living comfortably, peacefully and happily. In the life of the people and the nation, tolerance has become the benchmark in realizing the advance of a country, as reflected in the Charter of Medina that the Prophet Muhammad p.b.u.h formed a state on the basis of Islamic values, one of which was tolerance. A state or community will embrace safety and peace once its people live in mutual tolerance. In this study, there were three questions needed to be addressed: (1) What is the concept of tolerance in Islam?, (2) What is the attitude of tolerance between religious believers and social tolerance according to Islamic religious education lecturers at UIN Ar-Raniry Banda Aceh? and (3) How is the response of the Islamic religious education lecturers of UIN Ar-Raniry Banda Aceh towards the study which concluded that the city of Banda Aceh was of low tolerance? This study used the qualitative approach with field research methods, employing primary and secondary data. The results of the study revealed that the main criterion in defining religious tolerance was found in the Qur’an Surah al-Kafirun verse 6, while that in defining the social tolerance was in Surah an-Nisaa verse 86. The attitude of tolerance that the Prophet p.b.u.h had shown on various occasions was very comprehensive regardless of place and person, in any capacity. Therefore, the attitude of tolerance of the Prophet p.b.u.h had become a reference for every community to this day and he was also dubbed as the role model (Uswatun Hasanah). Responding to the finding of low tolerance in the city of Banda Aceh from a study, most respondents, however, believed otherwise. They agreed that Banda Aceh has already been a very tolerant city in terms of religious and social aspects in Indonesia. Thus, such low tolerance could not be generalized to all aspects and concluded that the city of Banda Aceh was an intolerant city or had a low tolerance level.